2021
DOI: 10.5267/j.uscm.2021.6.011
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the effect of supplier-company's long-term commitment, communication and strategy on supply chain performance in manufacturing sector

Abstract: The purpose of this study is to find answers to the research problem posed, namely the implementation of the long-term cooperation strategy between suppliers and companies through supplier commitment factors with companies and supplier communication with companies that can improve the company's supply chain performance. The populations in this study are suppliers of manufacturing companies listed on the Indonesia Stock Exchange (BEI) in 2016-2020. Data were collected using a questionnaire containing questions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 1 publication
0
4
0
Order By: Relevance
“…Cost [37][38][39][40][41][42][43][44][45][46][47][48], innovation capability [49][50][51][52][53][54][55][56][57][58][59], quality [60][61][62][63][64][65][66][67][68][69][70][71], service capability [57-59,72-79], long-term cooperation [80][81][82][83][84][85][86][87][88], environmental management system [89][90][91][92][93][94][95][96]...…”
Section: Case Studymentioning
confidence: 99%
“…Cost [37][38][39][40][41][42][43][44][45][46][47][48], innovation capability [49][50][51][52][53][54][55][56][57][58][59], quality [60][61][62][63][64][65][66][67][68][69][70][71], service capability [57-59,72-79], long-term cooperation [80][81][82][83][84][85][86][87][88], environmental management system [89][90][91][92][93][94][95][96]...…”
Section: Case Studymentioning
confidence: 99%
“…Due to intense competition, business managers must develop new models for managing products, and information flows are critical for all parties (Watts, 2020), including suppliers, manufacturers, distributors, retailers, and customers. Production of low-cost, highquality products has given rise to a concept of supply chain management (Mulyaningsiha et al, 2021).…”
Section: Relation Between Organisational Change and Business Alliance...mentioning
confidence: 99%
“…Furthermore, the function and existence of the long-term collaboration strategy's antecedents are crucial factors in determining supply chain performance (Watts, 2020). Interestingly, the influence analysis showed that communication significantly influences supply chain performance more than commitment (Mulyaningsiha et al, 2021). Moreover, Sukhawatthanakun (2022a) stated that entrepreneurs should implement ethical norms to reduce problems with the products they offer customers to sustain trust in the marketing process.…”
Section: Relation Between Organisational Change and Business Alliance...mentioning
confidence: 99%
“…In overcoming the problem of plastic waste in 10 Provinces and Capital cities, the policy model developed by Edwards is used [18]. According to him, the success of public policy implementation is influenced by several factors; a).…”
Section: Theory and Conceptmentioning
confidence: 99%